Childhood intussusception in Ile-ife: What has changed? - Ademola Olusegun Talabi; Oludayo Adedapo Sowande; Chiduziem Amarachukwu Etonyeaku; Olusanya Adejuyigbe (Wolters Kluwer Medknow Publications, 2013)
Background: Intussusception is one of the most common causes of intestinal obstruction in children. While the outcome has improved in the developed nations, the same cannot be said of the developing countries, more especially in the sub-Saharan region. This study aims to review our current experience in the management of childhood intussusception and factors affecting surgical outcome at the Obafemi Awolowo University Teaching Hospitals Complex Ile-Ife. Patients and Methods: This was a retrospective study of 78 patients treated for intussusception at paediatric surgical unit of Obafemi Awolowo University Teaching Hospitals Complex Ile-Ife between January 1993 and December 2011. The case notes of the patients were retrieved and the following information was recorded: Demographic characteristics, month of occurrence, clinical presentation, investigations, and management as well as the post-operative outcome. The patients were divided into two groups in terms of outcome. Results: There were 58 males and 20 females (M:F = 2.9-1). The age of most of the patients was between 3 months and 9 months with peak incidence at 6 months. Most patients 46 (58.9%) were seen during the dry season of December to April. Only six patients (7.7%) presented within 24 hours of onset of illness. More than half of the patients presented after 24 hours. Passage of red currant stool, vomiting, abdominal pain, fever, and abdominal distension, passage of watery stool, anal protrusion and palpable abdominal mass in various combinations were the clinical features. All the patients had surgical operations. The most common type of intussusception was ileo-colic type in 64 patients (82.1%). Intestinal resection rate was 41%. The overall mortality rate was 15.4%. Conclusion: There was a delay in presentation of children with intussusception with high post-operative mortality.